Seismic Performance and Flexural Capacity Analysis of Embedded Steel Plate Composite Shear Wall Structure with Fiber-Reinforced Concrete in the Plastic Hinge Zone - Junlong Li; Guoqiang He; Jianbo Tian (Buildings)
Due to its high axial bearing capacity and good ductility, the embedded steel plate composite shear wall structure has become one of the most widely used lateral force-resisting structural members in building construction. However, bending failure is prone to occur during strong earthquakes, and the single energy dissipation mechanism of the plastic hinge zone at the bottom leads to the concentration of local wall damage. To improve the embedded steel plate composite shear wall structure, the plastic hinge zone of the composite shear wall is replaced by fiber-reinforced concrete (FRC) and analyzed by ABAQUS finite element simulation analysis. Firstly, the structural model of the embedded steel plate composite shear wall structure with FRC in the plastic hinge zone is established and the accuracy of the model is verified. Secondly, the effects of steel ratio, longitudinal reinforcement ratio, and FRC strength on the bearing capacity of composite shear walls are analyzed by numerical simulation. Finally, a method for calculating the embedded steel plate composite shear wall structure with FRC in the plastic hinge zone is proposed. It is shown that the displacement and load curves and failure modes of the model are basically consistent with the experimental results, and the model has high accuracy. The axial compression ratio and FRC strength have a great influence on the bearing capacity of composite shear walls. The calculation formula of the normal section bending capacity of the embedded steel plate composite shear wall structure with FRC in the plastic hinge zone is proposed. The calculated values of the bending capacity are in good agreement with the simulated values, which can provide a reference for its engineering application.